2011
DOI: 10.1021/jf104837w
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Supercritical Carbon Dioxide Extract and Its Isolated Carnosic Acid from Rosmarinus officinalis Leaves

Abstract: Rosemary (Rosmarinus officinalis) leaves possess a variety of bioactivities. Previous studies have shown that the extract of rosemary leaves from supercritical fluid extraction inhibits the expression of inflammatory mediators with apparent dose-dependent responses. In this study, three different extraction conditions (5000 psi at 40, 60, and 80 °C) of supercritical carbon dioxide (SC-CO(2)) toward the extraction of antioxidants from rosemary were investigated. Furthermore, simultaneous comparison of the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 38 publications
2
48
0
2
Order By: Relevance
“…The results obtained by Kuo et al [121] corroborate the studies carried out by Vicente et al [89] using rosemary leaves; the authors obtained high CA content in the extract in 1 h of extract ion by SFE. The antio xidant activity o f the extract increased with the ext raction time because the volatile oil is depleted from the vegetal matrix at the beginning of the process, and the phenolic co mpounds, which present higher antioxidant activity, are only later extracted.…”
Section: Supercritical Flui D Extracti On (Sfe)supporting
confidence: 82%
See 1 more Smart Citation
“…The results obtained by Kuo et al [121] corroborate the studies carried out by Vicente et al [89] using rosemary leaves; the authors obtained high CA content in the extract in 1 h of extract ion by SFE. The antio xidant activity o f the extract increased with the ext raction time because the volatile oil is depleted from the vegetal matrix at the beginning of the process, and the phenolic co mpounds, which present higher antioxidant activity, are only later extracted.…”
Section: Supercritical Flui D Extracti On (Sfe)supporting
confidence: 82%
“…Carnosic acid (CA) and carnosol are the major phenolic diterpenes present in rosemary ext racts obtained by SFE, as shown by Kuo et al [121]. The CA content obtained in the referred study was approximately 110 mg/g extract, resulting in IC 50 of 7.47 µg/cm 3 .…”
Section: Supercritical Flui D Extracti On (Sfe)mentioning
confidence: 55%
“…The presence of hesperidin as one of the major constituents in an ethanol extract, which was shown to be partially responsible for the antinociceptive activity of R. officinalis assayed in an arthritic model in rats was previously described (Martínez et al, 2009b). Flavonoids and phenolic acids isolated from several medicinal plants are considered to be responsible for the analgesic, anti-inflammatory and anti-spasmodic activities in experimental models of abdominal, arthritic and orofacial pain (Martínez et al, 2009a;Bonjardim et al, 2011;Kuo et al, 2011). Moreover, anti-inflammatory properties of the triterpenes have also been described in several studies (Liu, 1995;Má ñ ez et al, 1997;Costa et al, 2003;Maia et al, 2006a;Altinier et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Rosmarinic acid (RA) is used to treat bronchial asthma, peptic ulcers, cataract, arthritis, cancer and rheumatoid arthritis. It is found in large quantities in oregano, lemon balm, sage, marjoram, and rosemary (Kuo et al, 2011). Many studies have shown that rosemary extracts play important roles in antiinflammation, anti-tumor, and anti-proliferation in various in vitro and in vivo settings (Cheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%